Characterization of additional cytogenetic abnormalities in haematological patients upon disease relapse. - Chee, Joyce Yuen Yin. (2012)
The aim of this study was to investigate the cytogenetic abnormalities in patients with haematological disorders at the time of diagnosis and at relapse, as well as its clinical implications. Cytogenetic studies were performed on 150 patients with acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), chronic myeloid leukemia (CML) and multiple myeloma (MM). The patient’s age, sex, karyotype at diagnosis and relapse, and prognosis were considered. While some patients had normal karyotypes; others had abnormal karyotypes showing structural and numerical aberrations. Each disease group is associated with certain aberrations and some of these were found to occur in more than one disease type. Various chromosomal aberrations are age-group specific and have sex predilection, as well as prognosis. Some aberrations were found to be more common at relapse. Karyotypic shift and clonal evolution were also common features at relapse. In the majority of cases, they had common chromosomal abnormalities such as derivative chromosomes, deletions and additional material of unknown origin. However, consistent markers of the diseases, except for CML, were not found because recurring aberrations were only found in a small number of patients.